Pemerolehan Bahasa Pada Anak Usia 1 dan 7 Tahun yang Memiliki Gangguan Berbicara (Cadel) - Balqis, Amira; Turnip, Juli Patricia; Elvinasari, Maria Dopo (Peneliti.net, 2023)
Language permission in 1-7 year-olds with speech impairment (cadel) To know the rules of language permission in Indonesian, an adequate set of data is required to prove it based on existing theories. In this study, examples of Indonesian language authorization can certainly be found in children ages 1-7 with speech impairment (cadel), this will also be examined so that it is expected to know to what extent the concept of language authorization can be applied, and principles can be found. In addition, this time's research data collection technique was interview, which the researcher hereby interviewed the child with speech disorder (cadel). The main instrument in this study is that we researchers are assisted by the interview text already provided. At the time of data analysis techniques in conducting this study employed deceptive analysis techniques. The results of this study in 1-7 year-olds with speech impairment (cadel) show some aspects of language government. one aspect of permission that in can be like the pronunciation of an imperfect word.